Design and Characterization of a Cook‐Off Resistant High‐Energy Booster Explosive Based on CL‐20/FOX‐7. Issue 5 (7th March 2019) - Li, Xiaodong; Zhang, Ximing; Yang, Wu; Song, Changgui; Sun, Hongyan; Wang, Jingyu
Abstract: A cook‐off resistant high‐energy booster explosive based on hexanitrohexaazaisowurtzitane (CL‐20) and 1, 1‐diamino‐2, 2‐dinitroethylene (FOX‐7) was prepared by the solvent‐slurry process with ethylene‐vinyl acetate copolymer (EVA) and acrylate rubber (ACM) as binders. Small‐scale cook‐off test was used to select formulations that have cook‐off resistant ability and their performance were further compared. Scanning electron microscopy (SEM) was utilized to characterize the morphology and particle size of CL‐20, FOX‐7 and molding powders. The mechanical sensitivity, thermal decomposition performance, and detonation velocity of the CL‐20/FOX‐7 boosters were also measured and analyzed. The results showed that the mechanical sensitivity of CL‐20/FOX‐7 boosters was significantly lower than those of CL‐20 based PBX without FOX‐7. The maximum measured detonation velocity of the booster is 8576 m ⋅ s −1 . These combined properties indicate that CL‐20/FOX‐7 booster can be used as an insensitive booster. Abstract :